2015
DOI: 10.2319/042915-295.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the oropharyngeal airway of Class II patients treated with the mandibular anterior repositioning appliance

Abstract: Objective: To evaluate the effects of functional appliance treatment on the oropharyngeal airway volume, airway dimensions, and anteroposterior hyoid bone position of growing Class II patients. Materials and Methods: Twenty Class II white patients (mean age, 11.7 6 1.75 years) treated with the MARA followed by fixed appliances were matched to an untreated control sample by cervical vertebrae maturation stage at pretreatment (T1) and posttreatment (T2) time points. Cone beam computed tomography scans were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 33 publications
3
23
1
1
Order By: Relevance
“…In particular, a similar finding was observed in two previous CBCT studies where the effect of functional appliances was compared to a control group; an enlargement of the oropharyngeal volume was reported as well. 24,26 To verify that these volume increments would be maintained with time, it would be necessary to have a long-term follow-up. However, no long-term CBCTs are available in this retrospective study, for evident ethical reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a similar finding was observed in two previous CBCT studies where the effect of functional appliances was compared to a control group; an enlargement of the oropharyngeal volume was reported as well. 24,26 To verify that these volume increments would be maintained with time, it would be necessary to have a long-term follow-up. However, no long-term CBCTs are available in this retrospective study, for evident ethical reasons.…”
Section: Discussionmentioning
confidence: 99%
“…As the study is retrospective in nature, only healthy individuals were included in the study, and the results interpreted only the natural anatomic variations that were present, but no pharyngeal pathology was considered. Although previous studies[ 2 16 ] showed that weak correlation existed between the sagittal linear measurements on the lateral cephalogram and cross-sectional area measurements in CBCT which is more appropriate for the measurement of airway patency, a recent systematic review[ 17 ] suggested that no ideal diagnostic tool exists to reliably screen the airway patency and adenoid hypertrophy. More research is required to suggest a diagnostic tool which is more reliable, low risk, and highly acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…From the literature, it has been proposed that the dimensions of oropharynx and nasopharynx may get varied with craniofacial growth or by functional appliance therapy. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with a constriction of the oropharyngeal pathways, which could be explained by a more pronounced position of the tongue base and the hyoid bone. 25,48 a b Clinical studies show that functional device therapy increases the volume of the oropharyngeal pathways and the anteroposterior position of the hyoid bone, and helps patients with Class-II malocclusions 32,58,68,70 . (Fig.…”
Section: Can a Two-phase Treatment Increase The Volume Of The Airways?mentioning
confidence: 99%
“…Depending on the individual case of the patient, clinicians may, in particular, aim to decrease the risk of trauma of the maxillary incisors 66 , decrease the risk of root resorptions 62 , improve the quality of life 24 , increase the volume of the airways 32,58,68,70 , and improve any obstructive sleep disorders 14,30,65 .…”
Section: The Dentoalveolar Compensation Phenomenonmentioning
confidence: 99%